“Maintain Your Hope and Know That You Are Loved.” Mr. Anthony Albanese’s Discursive Construction of Collective Emotional Resilience - Zubrzycka-Czarnecka, Aleksandra (Qualitative Sociology Review, 2024)
This paper employs Stephanie Paterson’s empathic policy analysis framework to explore the discursive construction of emotional resilience. The research conducted for the paper focuses on Australian Prime Minister Anthony Albanese’s notion of emotional resilience during a press conference he delivered on October 15, 2023, in the context of the Voice referendum. Mr. Albanese discursively frames the concept of emotional resilience as emotional stability that builds the community’s resistance to crisis situations, enables progress, and avoids division. The study identifies two emotional discourses influencing this portrayal of emotional resilience: (1) a discourse of emotional stability among opponents of the Voice referendum and (2) a discourse of emotional stability among supporters of the referendum. The article analyzes the assumptions underlying this representation and the silences—that which has been left unspoken or implied—associated with it.